2019
DOI: 10.3138/jmvfh.2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions for supporting partners of military Veterans with PTSD

Abstract: Introduction: Partners of military Veterans with post-traumatic stress disorder (PTSD) and other mental health difficulties can themselves develop difficulties with stress, well-being, and secondary trauma. Various interventions exist which involve partners of military personnel, but very few with an explicit focus on the partners’ well-being. This article aims to conduct a systematic review of these interventions and outline the range of interventions and the outcomes measured. Methods: We conducted a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Th is understanding of being a vigilant caregiver could provide valuable insight into family-and couple-based interventions, such as those proposed by Turgoose and Murphy. 38 Th e fi ndings from this study suggest that many forms of intervention, such as psychoeducation, Internet-based interventions, and residential retreats, are successful in improving the mental well-being of intimate partners; however, group-based interventions were especially highlighted for the connections formed between participants. 38 Sharing an understanding of the diffi culties faced while supporting a Veteran, as well as unpacking their role as a vigilant caregiver in a social context, may have contributed to the connections that were formed and could form the basis for future interventions.…”
Section: Discussionmentioning
confidence: 76%
“…Th is understanding of being a vigilant caregiver could provide valuable insight into family-and couple-based interventions, such as those proposed by Turgoose and Murphy. 38 Th e fi ndings from this study suggest that many forms of intervention, such as psychoeducation, Internet-based interventions, and residential retreats, are successful in improving the mental well-being of intimate partners; however, group-based interventions were especially highlighted for the connections formed between participants. 38 Sharing an understanding of the diffi culties faced while supporting a Veteran, as well as unpacking their role as a vigilant caregiver in a social context, may have contributed to the connections that were formed and could form the basis for future interventions.…”
Section: Discussionmentioning
confidence: 76%
“…Military families face specific challenges associated with service; these challenges may differ based on whether the service member is still serving or has transitioned from the military. For serving families, issues include family relationship strain and separation due to deployment; interruption to children's education, difficulties for partners in gaining employment, and lack of social support and extended family networks; attributable to relocation, as well as service‐related injury and family member health issues (Manser, 2020; Tan, 2020; Turgoose & Murphy, 2019). For families with members no longer serving, posttransition challenges may include housing, employment, and financial stability, loss of identity and social networks for the former‐serving member, and service‐related health issues such as PTSD and physical injury (Miller et al., 2019; Muir, 2018; Tan, 2020; The Centre for Social Justice, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Carers may need to be hypervigilant, to identify and manage environmental and social situations that could trigger reactions from care recipients living with service‐related PTSD, trauma or brain injury (Miller et al., 2019; Saban et al., 2016). Family carers of veterans may also experience secondary trauma or psychological impacts (Turgoose & Murphy, 2019). Qualitative research into understanding the experiences of carers veterans with posttraumatic stress demonstrates that some carers feel socially disconnected and that there is generally a lack of understanding of their role as carers (Waddell et al., 2016) – feelings which may serve as impediments to their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce PTSD symptoms, a meta-analysis suggested that iCBT for PTSD was efficacious, and only one study was analyzed based on a military sample ( Niemeyer et al, 2020 ). One review included 12 studies to access the interventions for supporting partners of military veterans with PTSD, among which only one was based on IBI ( Turgoose and Murphy, 2019 ). However, IBIs in other groups were tested as effective in supporting informal caregivers ( Sherifali et al, 2018 ), which helped us to see the potential of IBI on veterans with PTSD in our study.…”
Section: Introductionmentioning
confidence: 99%